1994
DOI: 10.1002/j.1460-2075.1994.tb06721.x
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT box binding protein NF-Y facilitates in vivo recruitment of upstream DNA binding transcription factors.

Abstract: NF‐Y binds a CCAAT motif found in many eukaryotic polymerase II‐dependent promoters. In the HLA‐DRA promoter it has been demonstrated that stereo‐specific alignment between this motif and the upstream elements X1 and X2 is required for activation. To study the underlying mechanism for this requirement, a panel of transfected cell lines that maintained integrated, wild‐type and mutant promoters were analyzed by in vivo genomic footprinting. Cell lines harboring a mutated CCAAT element exhibited a loss of intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
2
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(137 citation statements)
references
References 79 publications
11
123
2
1
Order By: Relevance
“…There are also a number of additional possible phosphorylation sites throughout the protein, which is consistent with our previous finding that the CA-I activity can be phosphorylated (Sun et al, 1993). The CCAl clone has been mapped to a position near the bottom of chromosome 2 next to marker Athb-7 at 94.8 centimorgans on a yeast artificial chromosome-anchored physical map (Zachgo et al, 1996). We have also demonstrated that the CCAl protein is transported to nuclei in vivo, and this is consistent with its proposed function as a transcription factor.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There are also a number of additional possible phosphorylation sites throughout the protein, which is consistent with our previous finding that the CA-I activity can be phosphorylated (Sun et al, 1993). The CCAl clone has been mapped to a position near the bottom of chromosome 2 next to marker Athb-7 at 94.8 centimorgans on a yeast artificial chromosome-anchored physical map (Zachgo et al, 1996). We have also demonstrated that the CCAl protein is transported to nuclei in vivo, and this is consistent with its proposed function as a transcription factor.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of a CCAAT box downstream of the conserved CCA1 binding sequence (Table 1) also raises the possibility that CCA1 could interact with a CCAAT-box binding protein. The CCAAT motif occurs in many eukaryotic promoters, and it has been proposed that factors binding to this sequence can facilitate recruitment of transcription factors binding upstream of this sequence (Wright et al, 1994). The proposed role in transcriptional activation of the protein(s) binding to the AAA A / C AATCTA region contrasts with our earlier proposal that CA-1 might act to repress transcription in dark-grown seedlings (Sun et al, 1993).…”
Section: Wt2 -G-gtt-----g-g--------g--t-c---------------g-gtt-----g-gcontrasting
confidence: 66%
“…It is also in agreement with in vivo footprint experiments, which have demonstrated that there is no clear footprint on the W/S box, whereas there is stable occupation of the X, X2, and Y boxes (61,62). Moreover, disruption of the S box in stably transfected reporter gene constructs does not alter the in vivo footprint pattern at the X, X2, and Y boxes (26). Finally, the precise spacing constraint also suggests that the S box serves a function distinct from the other cis-acting elements of MHCII promoters.…”
Section: M1/m2 M4 and M2/m4)supporting
confidence: 90%
“…Finally, we propose that the NF-Y factor could organize the binding of the nearby factors. Such a situation is not unprecedented and previous report have pointed to the possibility that NF-Y might facilitate in vivo recruitment of upstream DNA binding transcription factors (Wright et al, 1994;Coustry et al, 1995). The resolution of this problem will await the puri®cation of the factor binding to the CCRE and the establisment of an in vitro assay to study these multiple interactions.…”
Section: Discussionmentioning
confidence: 99%